Autobiographical memory and structural brain changes in chronic phase TBI. (April 2017) - Esopenko, Carrie; Levine, Brian
Abstract: Traumatic brain injury (TBI) is associated with a range of neuropsychological deficits, including attention, memory, and executive functioning attributable to diffuse axonal injury (DAI) with accompanying focal frontal and temporal damage. Although the memory deficit of TBI has been well characterized with laboratory tests, comparatively little research has examined retrograde autobiographical memory (AM) at the chronic phase of TBI, with no prior studies of unselected patients drawn directly from hospital admissions for trauma. Moreover, little is known about the effects of TBI on canonical episodic and non-episodic (e.g., semantic) AM processes. In the present study, we assessed the effects of chronic-phase TBI on AM in patients with focal and DAI spanning the range of TBI severity. Patients and socioeconomic- and age-matched controls were administered the Autobiographical Interview (AI) (Levine, Svoboda, Hay, Winocur, & Moscovitch, 2002) a widely used method for dissociating episodic and semantic elements of AM, along with tests of neuropsychological and functional outcome. Measures of episodic and non-episodic AM were compared with regional brain volumes derived from high-resolution structural magnetic resonance imaging (MRI). Severe TBI (but not mild or moderate TBI) was associated with reduced recall of episodic autobiographical details and increased recall of non-episodic details relative to healthy comparison participants. There were no significant associations between AM performance and neuropsychological or functional outcome measures. Within the full TBI sample, autobiographical episodic memory was associated with reduced volume distributed across temporal, parietal, and prefrontal regions considered to be part of the brain's AM network. These results suggest that TBI-related distributed volume loss affects episodic autobiographical recollection.